Tinjauan Literatur Efek Neuroprotektif dan Anti-Penuaan Kitosan dan Chitooligosakarida (Cos) Yang Berasal dari Spons Laut Kelas Demospongiae terhadap Penyakit Alzheimer - Inka Abilia Marsha; Herin Setianingsih; Ni Komang Sri Dewi Untari; Liliawanti Liliawanti (Jurnal Ners, 2026)
This study aims to analyze scientific evidence regarding the neuroprotective and anti-aging effects of chitosan and COS in relation to the prevention and therapy of Alzheimer's disease. This study used a narrative literature review approach to scientific articles from 2015–2025 obtained from PubMed, Scopus, and Google Scholar. The included articles discussed the biological activities of chitosan or COS against oxidative stress, inflammation, and neuronal protection in in vitro and in vivo models. A total of ten journals met the analysis criteria. The results of the study indicate that chitosan acts as a drug delivery system that effectively penetrates the blood–brain barrier, increases drug bioavailability, and reduces the toxicity of active substances such as galantamine and rivastigmine. COS exhibits direct biological activity on nerve cells through inhibition of the NF-κB and MAPK inflammatory pathways, increased Nrf2/HO-1 expression, and activation of the PI3K/Akt/GSK3β pathway. These two compounds also reduce ROS, MDA, IL-1β, and TNF-α levels and increase antioxidant enzymes (SOD, GSH-Px, CAT). These effects contribute to neuronal protection, improved cognitive function, and slowed the aging process of nerve cells. Based on this study, it was concluded that chitosan and COS from marine sponges of the class Demospongiae have great potential as neuroprotective and anti-aging agents through antioxidant, anti-inflammatory, and antiapoptotic mechanisms. These compounds hold promise as adjunctive therapies for Alzheimer's, but further molecular and clinical studies are needed to confirm their effectiveness and safety in humans.